To determine which equation is true when \( k = -15 \), we can substitute \( k \) into each equation and see which one is satisfied.
Checking each equation:
F: \( 3k - 11 = -34 \)
- Substitute \( k = -15 \): \[ 3(-15) - 11 = -34 \]
- Calculate: \[ -45 - 11 = -34 \] \[ -56 \neq -34 \text{ (False)} \]
G: \( -53 + 4k = 7 \)
- Substitute \( k = -15 \): \[ -53 + 4(-15) = 7 \]
- Calculate: \[ -53 - 60 = 7 \] \[ -113 \neq 7 \text{ (False)} \]
H: \( \frac{k}{3} + 17 = 12 \)
- Substitute \( k = -15 \): \[ \frac{-15}{3} + 17 = 12 \]
- Calculate: \[ -5 + 17 = 12 \] \[ 12 = 12 \text{ (True)} \]
J: \( \frac{k}{5} + 2.5 = 0.5 \)
- Substitute \( k = -15 \): \[ \frac{-15}{5} + 2.5 = 0.5 \]
- Calculate: \[ -3 + 2.5 = 0.5 \] \[ -0.5 \neq 0.5 \text{ (False)} \]
Conclusion:
The only equation that holds true when \( k = -15 \) is H: \( \frac{k}{3} + 17 = 12 \).